Meconium Aspiration Syndrome, Hypoxic-Ischemic Encephalopathy and Therapeutic Hypothermia-A Recipe for Severe Pulmonary Hypertension? - Deepika Sankaran; Jessa Rose A. Li; Satyan Lakshminrusimha (MDPI AG, 2024)
Hypoxic-ischemic encephalopathy (HIE) is the leading cause of mortality among term newborns globally. Infants born through meconium-stained amniotic fluid are at risk of developing meconium aspiration syndrome (MAS) and HIE. Simultaneous occurrence of MAS and HIE is a perilous combination for newborns due to the risk of persistent pulmonary hypertension of the newborn (PPHN). Moreover, therapeutic hypothermia (TH), which is the current standard of care for the management of HIE, may increase pulmonary vascular resistance (PVR) and worsen PPHN. Infants with MAS and HIE require close cardiorespiratory and hemodynamic monitoring for PPHN. Therapeutic strategies, including oxygen supplementation, ventilation, use of surfactant, inhaled nitric oxide and other pulmonary vasodilators, and systemic vasopressors, play a critical role in the management of PPHN in MAS, HIE, and TH. While TH reduces death or disability in infants with HIE, infants with MAS and HIE undergoing TH need close hemodynamic monitoring for PPHN.